Adult Variant of Self-healing Cutaneous Mucinosis in a Patient with Epilepsy - Reza Yaghoobi; Arezou Bagherzade; Maryam Aliabdi; Pavin Kheradmand; Afshin Kazerouni; Amir Feily (Interna Publishing, 2016)
A 52-year-old woman was admitted with a 3 weeks history of periorbital edema and lips swelling. She developed several subcutaneous firm erythematous papules and nodules on the face, scalp and two indurated plaques on the upper back and left forearm. These lesions grew rapidly. The patient had a positive history of epileptic seizures since childhood. General examination was normal. There was a mild pitting edema on her hands and feet. Laboratory data were within normal limits. Histopathological examination revealed a well circumscribed accumulation of mucin in the dermis. Alcian blue stain was positive. Clinical and histopathological findings followed by spontaneous resolution of the lesions within a period of 4 months was compatible with diagnosis of self-healing cutaneous mucinosis. Herein we report the first case of self-healing cutaneous mucinosis associated with epilepsy.